(untitled) (Medico Legal Update, 2020)
Objective Male infertility is a term in which the male is not capable to attain pregnancy in a female. It occurs due to a lack of semen and low-quality semen. Semen Quality is referred to as a surrogate measure of male fecundity. This study aims to assess the frequency of sperm factors in infertile men in Thi-Qar City. Materials and Methods: This study involved an infertile couple, seminal fluid analysis (SFA) was done to evaluate male factors. Males with normal seminal fluid parameters were excluded. Regarding male, SFA was examined according to WHO 2010. Information such as age, duration of infertility and type of infertility were taken Results Among the percentage of abnormal sperm parameters for infertile couples in which the largest percentage was for asthenozoospermia that represent 66.70% of all infertile males. The second sperm abnormality is 12.13% for oligoasthenozoospermia. Asthenoteratozoospermia and oligoasthenoteratozoospermia have the same percentage (4.4). Azoospermia represents 6.7% while the lower percentage for teratozoospermia. Conclusions largest percentage was for asthenozoospermia that represents 66.70% of all infertile males .